The Effect of Intellectual Capital Management on The Use of Management Accounting Practices in The SME Consumer Goods Industry in East Java - Kristina, Natalia; Widyaningdyah, Agnes Utari; Rachmawati, Dyna (Ekonomi Bisnis, 2021)
Increased business competition of Small and Moderate Enterprises, SME, makes each business unit eager to compete. The business units realize the achievement by managing the intellectual capital accurately and making a decision based on information of Accounting Practice Management. This research aims to determine the influence of intellectual capital management toward the accounting practice management of SMEs in good consumable industries in East Java. The researchers took the sample with a non-probability sampling technique. Then, they analyzed the data with Ordinary Least Square regression (OLS). The respondents were SME doers. They were 126 respondents with various backgrounds. This research used other approaches by adding a controlled variable, the years of business. The results statistically found a positive and significant influence of intellectual capital management with accounting practice management. Thus, Small and Moderate Enterprises, while managing their intellectual capital maximally, could influence the implementation of accounting practice management to provide supportive information in making an organizational decision. On the other hand, the years of business in this research did not significantly influence managerial practice in SMEs.